(untitled) (The Review of Diabetic Studies, 2025)
Background: The integration of three-dimensional (3D) printing into orthopaedic surgery has revolutionized joint replacement by enabling patient-specific implant design and precision-driven reconstruction. Objectives: This systematic review aimed to evaluate the clinical outcomes, design strategies, and material performance of 3D-printed custom joint replacement implants across multiple anatomical sites, including the hip, knee, ankle, temporomandibular joint (TMJ), and upper extremities. Methods: Following PRISMA 2020 guidelines, twelve clinical studies published between 2017 and 2025 were systematically reviewed. Data regarding patient demographics, implant material, surgical accuracy, complication rates, and postoperative functional outcomes were extracted and synthesized narratively. Results: The majority of studies demonstrated substantial improvements in joint function and patient-reported outcome measures, including Harris Hip Score, Knee Society Score, and FAOS. Custom 3D-printed implants yielded high precision in alignment correction and osseointegration, with reported infection rates below 5%. Titanium and tantalum-based prostheses showed enhanced mechanical stability and bone ingrowth. Long-term follow-up studies confirmed sustained implant stability, with minimal migration beyond 0.1 mm/year. Conclusion: Evidence supports the clinical efficacy and safety of 3D-printed custom joint implants in complex reconstructive procedures. These technologies optimize anatomical restoration, reduce surgical time, and improve postoperative recovery. However, heterogeneity in design protocols and limited randomized controlled trials warrant further multicenter research.